2021
DOI: 10.3390/ijerph18020562
|View full text |Cite
|
Sign up to set email alerts
|

Is the Association between Postpartum Depression and Early Maternal–Infant Relationships Contextually Determined by Avoidant Coping in the Mother?

Abstract: This study analyzes the moderating role of avoidant coping (in early pregnancy) in the relationship between postpartum depressive (PPD) symptoms and maternal perceptions about mother–baby relations and self-confidence. Participants were 116 low-risk obstetric mothers (mean age = 31.2 years, SD = 3.95, range 23–42) who received care and gave birth at a Spanish public hospital. Measurements were made at two points in time: at first trimester of pregnancy (maternal avoidance coping) and four months after childbir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
4
0
1
Order By: Relevance
“…Furthermore, the risk of recurrence was approximately 40% in either subsequent postpartum or non-postpartum. In addition to the increasing incidence, PPD was identified to negatively influence the physical and mental wellbeing of women [ 7 ], the behavioral and emotional development of infants [ 11 ], and the relationship with spouse and other family members [ 12 ]. Owing to the high prevalence and detrimental consequences, PPD has been identified as one of the severe global public health issues in the last decade [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the risk of recurrence was approximately 40% in either subsequent postpartum or non-postpartum. In addition to the increasing incidence, PPD was identified to negatively influence the physical and mental wellbeing of women [ 7 ], the behavioral and emotional development of infants [ 11 ], and the relationship with spouse and other family members [ 12 ]. Owing to the high prevalence and detrimental consequences, PPD has been identified as one of the severe global public health issues in the last decade [ 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kegagalan adaptasi ini mempengaruhi psikologi ibu dan menyebabkan depresi pasca melahirkan. Ibu yang mengalami depresi pasca melahirkan tidak dapat merawat bayinya, kurangnya rasa aman dalam merawat bayi, gizi buruk yang dapat menyebabkan bayi kurang gizi dan mempengaruhi tumbuh kembang bayi, mempengaruhi kedekatan ibu dan bayi serta memiliki efek negatif pada anak-anak sebagai orang dewasa (Puente et al, 2021).…”
Section: Pendahuluanunclassified
“…In both postpartum and non-postpartum women, the risk of recurrence was approximately 40%. Along with increasing prevalence, research has shown that PPD is harmful to the health and mental well-being of women [7], infants' behavioral and emotional development [10], and relationships with partners and family members [11]. Prevalence and consequences of PPD make it one of the most serious global public health issues of the last decade [7], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Postpartum depression literacy is not currently assessed using a standardized instrument within the context of mental health literacy. Postpartum depression literacy has been assessed in only two studies, neither of which used a specific measurement: They used three vignettes that met the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-V) criteria for a major depressive episode in their study [10]. There were 22 True/False/Don't Know questions in Fonceca et al Portuguese.…”
Section: Introductionmentioning
confidence: 99%